Theophylline as an Add-On to Thrombolytic Therapy in Acute Ischemic Stroke: A Randomized Placebo-Controlled Trial. Issue 7 (July 2020) - Modrau, Boris; Andersen, Grethe; Mikkelsen, Irene Klærke; Nielsen, Anne; Hansen, Mikkel Bo; Johansen, Martin Berg; Eskildsen, Helle Wulf; Povlsen, Jan Plougmann; Yavarian, Yousef; Mouridsen, Kim; Østergaard, Leif; Bach, Flemming Winther; et al.
Abstract : Background and Purpose: Delayed recanalization increases the risk of infarct growth and poor clinical outcome in acute ischemic stroke. The vasoactive agent theophylline has shown neuroprotective effects in animal stroke models but inconclusive results in case series and randomized clinical trials. The primary objective of this study was to evaluate whether theophylline, as an add-on to thrombolytic therapy, is safe and effective in acute ischemic stroke patients. Methods: The TEA-Stroke trial (The Theophylline in Acute Ischemic Stroke) was an investigator-initiated 2-center, proof-of-concept, phase II clinical study with a randomized, double-blinded, placebo-controlled design. The main inclusion criteria were magnetic resonance imaging–verified acute ischemic stroke, moderate to severe neurological deficit (National Institutes of Health Stroke Scale score of ≥4), and treatment with thrombolysis within 4.5 hours of onset. Participants were randomly assigned in the ratio 1:1 to either 220 mg of intravenous theophylline or placebo. The co-primary outcomes were early clinical improvement on the National Institutes of Health Stroke Scale score and infarct growth on magnetic resonance imaging at 24-hour follow-up. Results: Theophylline as an add-on to thrombolytic therapy improved the National Institutes of Health Stroke Scale score at 24 hours by mean 4.7 points (SD, 5.6) compared with an improvement of 1.3 points (SD, 7.5) in the control group ( P =0.044). Mean infarct growth was 141.6% (SD, 126.5) and 104.1% (SD, 62.5) in the theophylline and control groups, respectively ( P =0.146). Functional independence at 90 days was 61% in the theophylline group and 58% in the control group ( P =0.802). Conclusions: This proof-of-concept trial investigated theophylline administration as an add-on to thrombolytic therapy in acute ischemic stroke. The co-primary end points early clinical improvement and infarct growth at 24-hour follow-up were not significantly different after post hoc correction for multiplicity (Bonferroni technique). The small study size precludes a conclusion as to whether theophylline has a neuroprotective effect but provides a promising clinical signal that may support a future clinical trial. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: EudraCT number 2013-001989-42. Abstract : Supplemental Digital Content is available in the text.